The Role of Human Resources Management in Improving Teacher Innovation and Creativity in Madrasahs - Rosdiana, Aida; Khuzaini; Zamrudi, Zaky; Zainul, M.; Zuana, Muhammad Mujtaba Mitra (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
Human resources are crucial and strategic in bringing expertise, knowledge, and creativity through innovation to improve the performance of educational organizations. Teachers, as potential assets, require efforts to continuously improve their knowledge, education, skills, discipline, and mental attitude. This study aims to analyze human resource management strategies and practices that can encourage teacher innovation and creativity in madrasah. The method used in this research is descriptive qualitative, in which researchers try to interpret and understand events in the context experienced by the madrasah community. This qualitative research involves the collection and use of observations from various related case studies. The results showed that human resources (HR) has made a very significant contribution to encouraging innovation in madrasah. Different aspects, such as inspiring and encouraging creativity, facilitating collaboration, and supporting continuous learning and improvement, show that HR plays a crucial role in creating a work environment that supports the development of new ideas and the implementation of innovative solutions.